Economic evaluation of a guided and unguided internet-based CBT intervention for major depression: Results from a multicenter, three-armed randomized controlled trial conducted in primary care - Romero-Sanchiz, Pablo; Nogueira-Arjona, Raquel; García-Ruiz, Antonio J.; Luciano, Juan V.; Garcia Campayo, Javier; Gili, Margalida; Botella, Cristina; Baños, Rosa; Castro, Adoración; Lopez del Hoyo, Yolanda; Pérez Ara, Mª Ángeles; Modrego-Alarcón, Marta; et al. (Public Library of Science, 2017)
The aim of this study is to analyze the cost effectiveness at 12-month follow-up of the Internet-based CBT program "Smiling is fun" with (LITG) and without psychotherapist support (TSG) compared to usual care. The perspective used in our analysis is societal. A sample of 296 depressed patients (mean age of 43.04 years; 76% female; BDI-II mean score = 22.37) from primary care services in four Spanish regions were randomized in the RCT. The complete case and intention-to-treat (ITT) perspectives were used for the analyses. The results demonstrated that both Internet-based CBT interventions exhibited cost utility and cost effectiveness compared with a control group. The complete case analyses revealed an incremental cost-effectiveness ratio (ICER) of €-169.50 and an incremental cost-utility ratio (ICUR) of €-11389.66 for the TSG group and an ICER of €-104.63 and an ICUR of €-6380.86 for the LITG group. The ITT analyses found an ICER of €-98.37 and an ICUR of €-5160.40 for the TSG group and an ICER of €-9.91 and an ICUR of €496.72 for the LITG group. In summary, the results of this study indicate that the two Internet-based CBT interventions are appropriate from both economic and clinical perspectives for depressed patients in the Spanish primary care system. These interventions not only help patients to improve clinically but also generate societal savings.
CC BY
Keywords: Depresión mental - Tratamiento - Ensayos clínicos; Major depression; Primary care; Economic evaluation; Internet-based CBT